2006
DOI: 10.1161/01.atv.0000226543.77214.e4
|View full text |Cite
|
Sign up to set email alerts
|

Gene Variants of VAMP8 and HNRPUL1 Are Associated With Early-Onset Myocardial Infarction

Abstract: Variants in 2 genes were associated with early-onset MI: VAMP8, which is involved in platelet degranulation, and HNRPUL1, which encodes a ribonuclear protein. The identification of these variants could improve understanding of disease mechanisms and suggest novel drug targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 23 publications
3
47
1
1
Order By: Relevance
“…be associated with CHD in other studies: the ARIC risk allele of rs1010 in VAMP8 was associated with MI in three case-control studies 17 and the ARIC risk allele of rs20455 in KIF6 was associated with CHD in the placebo arms of two statin treatment studies. 18 For the other three SNPs (rs3900940 in MYH15, rs7439293 in PALLD, and rs2298566 in SNX19), the same risk allele was also associated with MI (P Ͻ 0.1) in the two casecontrol studies reported here (Table 8, supporting information, available online only) and with CHD in ARIC.…”
Section: Five Gene Variants Identify Risk Of Chd In Aricmentioning
confidence: 88%
See 2 more Smart Citations
“…be associated with CHD in other studies: the ARIC risk allele of rs1010 in VAMP8 was associated with MI in three case-control studies 17 and the ARIC risk allele of rs20455 in KIF6 was associated with CHD in the placebo arms of two statin treatment studies. 18 For the other three SNPs (rs3900940 in MYH15, rs7439293 in PALLD, and rs2298566 in SNX19), the same risk allele was also associated with MI (P Ͻ 0.1) in the two casecontrol studies reported here (Table 8, supporting information, available online only) and with CHD in ARIC.…”
Section: Five Gene Variants Identify Risk Of Chd In Aricmentioning
confidence: 88%
“…In estimating ranges of prior probability, we divided five SNPs into two groups. For the group of SNPs whose prior association with CHD had been described in published studies that adjusted for multiple hypothesis testing, we assumed a higher prior probability: False discovery rate analysis was used to account for multiple testing for the SNP in VAMP8, 17 and the Bonferroni method was used for the SNP in KIF6. 18 We assumed a lower prior probability of association for the SNPs in MYH15, PALLD, and SNX19; these were nominally associated with CHD in the two case-control studies of MI described in this report (Table 8, supporting information, available online only).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rs10757278G was independently associated with an increased risk for the incidence of CAD. Shiffman et al (2006) in a study of white Americans observed that the rs1010 locus in VAMP8, a gene involved in platelet degranulation (OR = 1.75; 90%CI = 1.17-2.62; P = 0.025), and the rs11881940 site in HNRPUL1, a gene encoding ribonuclease (OR = 1.92; 90%CI = 1.28-2.86; P = 0.0043), were associated with early-onset MI (Gabler et al, 1998;Polgar et al, 2002). However, we found that the rs1010 locus was not significantly correlated with CAD, a result inconsistent with those reported by Duan et al (2010), and this inconsistency may be due to differences in individual susceptibility to CAD.…”
Section: Discussionmentioning
confidence: 99%
“…22 Genotyping accuracy of the multiplex methodology and kPCR has been assessed in three previous studies by comparing genotype calls from multiplex OLA assays with those from real time kPCR assays for the same SNPs, and the overall concordance of the genotype calls from these two methods was >99% in each of these studies. [23][24][25] Primer sequences are available upon request.…”
Section: F9 Malmö and Endogenous Thrombin Potentialmentioning
confidence: 99%